Cementitious Material of Marble Waste Industry as Alternative Approach to Sustainable Concrete - Agil Fitri Handayani; Dzul Fikri Muhammad; Muhammad Arif Hidayatullah; Ninda Lufita Sari (Universitas Islam Raden Rahmat, Malang, 2023)
Concrete needs to use alternative materials to reduce cement content to limit the effect of carbon emissions. Marble dust as a waste of the marble industry has very fine grains. X-Ray Fluorescence (X-RF) method was conducted to determine the mineral properties of marble dust. Marble dust was found to contain 98.62% Calcium Oxide (CaO), 0.17% Sulfur Trioxide (SO3) and some elements in small levels. To determine the impact of marble dust on the mechanical characteristics of concrete, an experimental study was conducted. Test specimens were made with four different levels of marble dust, namely 0%, 5%, 10%, and 15%. The experimental results showed that the optimum usage was 6.62% by weight of cement which gave the advantage of increasing the compressive strength of concrete by 11.77%.